Святкування Маковія в селі Заворичі на Київщині - Шафранська, Г. (Народна творчість та етнографія, 2007)
This article is written in a form of literary memoirs, where the author gives her childhood recollections of the celebration of the big religious holiday Makoviy in the village Zavorychy, by her family, particularly her grandparents.